RESEARCH OF FIRE AND TECHNICAL CHARACTERISTICS OF NEW THERMAL INSULATION MATERIALS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The research paper presents the research results fire-technical characteristics of the developed tile materialsincluding porous materialsbased on sodium water-soluble silicates, glue-like derivatives of cellulose, microcrystalline cellulose, silicone,sodium carbosimethyl cellulose, finely dispersed wood shavings, dolomite, thermovermiculite, varieties of SiO2 and aluminum oxide.